2012
DOI: 10.1371/journal.pone.0044228
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Thalidomide-Specific Transcriptomics and Proteomics Signatures during Differentiation of Human Embryonic Stem Cells

Abstract: Embryonic development can be partially recapitulated in vitro by differentiating human embryonic stem cells (hESCs). Thalidomide is a developmental toxicant in vivo and acts in a species-dependent manner. Besides its therapeutic value, thalidomide also serves as a prototypical model to study teratogenecity. Although many in vivo and in vitro platforms have demonstrated its toxicity, only a few test systems accurately reflect human physiology. We used global gene expression and proteomics profiling (two dimensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
91
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(95 citation statements)
references
References 54 publications
2
91
1
Order By: Relevance
“…While there is no deus ex machina to solve all these challenges for the experimental toxicologist, the advent of pluripotent stem cells (PSCs) provides significant improvements (Baquié et al 2012;Leist et al 2008), enabling the impact of potentially toxic pesticides to be studied on virtually all types of cells without recourse to immortalized cell lines. Within the last 5 years, the European ESNATS consortium has been developing pluripotent stem cell-based toxicity tests, and first results demonstrate that such test systems may indeed become powerful tools (Krug et al 2013;Bolt 2013;Vojnits et al 2012;Kern et al 2013;Meganathan et al 2012;Kuegler et al 2010;Zimmer et al 2011a, b;Balmer et al 2012). The consortium has shown that complex functional endpoints can be transferred to in vitro test systems Kadereit et al 2012;Zimmer et al 2012).…”
mentioning
confidence: 99%
“…While there is no deus ex machina to solve all these challenges for the experimental toxicologist, the advent of pluripotent stem cells (PSCs) provides significant improvements (Baquié et al 2012;Leist et al 2008), enabling the impact of potentially toxic pesticides to be studied on virtually all types of cells without recourse to immortalized cell lines. Within the last 5 years, the European ESNATS consortium has been developing pluripotent stem cell-based toxicity tests, and first results demonstrate that such test systems may indeed become powerful tools (Krug et al 2013;Bolt 2013;Vojnits et al 2012;Kern et al 2013;Meganathan et al 2012;Kuegler et al 2010;Zimmer et al 2011a, b;Balmer et al 2012). The consortium has shown that complex functional endpoints can be transferred to in vitro test systems Kadereit et al 2012;Zimmer et al 2012).…”
mentioning
confidence: 99%
“…Toxicogenomics has been selected as an experimental approach as it enables unbiased, global profiling of the molecular biological response space (Richard, 2006;Edwards and Preston, 2008), without preselection of response parameters. For single chemicals, it has been shown that exposure results in chemical-specific, gene expression profiles (Hamadeh et al, 2002;Yang et al, 2007;Kiyosawa et al, 2010;Janssens et al, 2011;Piña and Barata, 2011;Meganathan et al, 2012;Theunissen et al, 2012). The hypothesis tested in the present study is whether specific MoAs have common gene expression profiles that can be used to classify compounds and whether compounds with multiple MoAs can be classified and distinguished from those with only one MoA.…”
Section: Introductionmentioning
confidence: 89%
“…the ideal test system will display all of the differentiated features and cellular functions found in intact organisms of various life stages, disease states, and conditions. Potential models for a cellular test system could use human embryonic stem cells (heSCs), or other types of stem/progenitor cells, in conjunction with protocols that allow these cells to differentiate along numerous organ-specific pathways (Leist et al, 2008;Kuegler et al, 2010;Wobus and löser, 2011;Zimmer et al, 2011Zimmer et al, , 2012Balmer et al, 2012;Meganathan et al, 2012).…”
Section: In Vitro Effects Batterymentioning
confidence: 99%